The Influence of Interactive Learning Media on Students' Learning Interest in Biology Subjects in Junior High Schools - Mariati, Suriani Lela (Trigin Institute, 2024)
This research investigates the influence of interactive learning media on students' learning interest in biology subjects within junior high schools. Utilizing a mixed-methods approach, the study combines quantitative assessments of academic performance through pre-tests and post-tests with qualitative data from student interviews and teacher focus groups. The findings reveal that students exposed to interactive learning tools, such as simulations and virtual labs, exhibit significantly higher levels of engagement and motivation compared to those taught through traditional methods. Enhanced comprehension of complex biological concepts and improved academic outcomes are notable results of this engagement. Furthermore, qualitative insights highlight the role of interactive media in fostering collaborative learning environments and empowering students to take an active role in their education. The study underscores the implications for educational practice and policy, advocating for the integration of interactive learning media into biology curricula and the necessity of professional development for educators. These findings contribute to the growing body of evidence supporting the effective use of technology in enhancing student learning experiences, ultimately promoting a deeper interest in science education among junior high school students. Interactive Learning Media; Student Engagement